People who inject drugs in Bangladesh — The untold burden!. (June 2019) - Khan, Sharful I.; Reza, Md Masud; Crowe, Suzanne M.; Rahman, Mustafizur; Hellard, Margaret; Sarker, Md Safiullah; Chowdhury, Ezazul Islam; Rana, A.K.M. Masud; Sacks-Davis, Rachel; Banu, Sayera; Ross, Allen G.
Abstract: The rates of both HIV and HCV are exploding among the People Who Inject Drugs (PWID) subpopulation in the People's Republic of Bangladesh. 5, 586 HIV confirmed cases have been reported since the first case of HIV was identified in 1989, of which, 865 new cases (15.5%) have been reported in the year 2017 alone. Among the new cases, 330 (38.2%) were from PWID population. The HCV prevalence is also high in Dhaka, with 40% of the PWID with unknown HIV status and 60.7% co-infected with HIV. The predominant HIV-1 strains circulating in the population are subtype C (41.4%) followed by CRF07 BC (24.2%), CRF01 AE (9.1), A1 (6.6%), and B (2.5%). HCV subtypes 3a and 3b are the most prevalent circulating strains (88.5%) among PWID. Harm reduction interventions particularly Needle Syringe Program (NSP) for PWID have been operating in Bangladesh since 1998. Opioid Substitution Therapy (OST) commenced in 2010 but only covers 2.9% of the total estimated PWID population in the country. A preliminary assessment of the needle/syringe sharing networks of HIV positive PWID was made in order to determine the HIV status among needle/syringe sharing partners. From a network of 36 HIV positive PWID seeds, 96 needle/syringe sharing partners were identified, of which 10 were HIV positive. Characterization of the nature of transmission within PWID networks is required in order to develop clinical services aimed at this vulnerable subpopulation and to halt the epidemic.